The Role of Social Capital in the Response and Recovery Process of Post-Disaster Affected Communities - Hafizha Ilma Qadriina; Herdis Herdiansyah; Bagus Aryo (GoAcademica Research & Publishing, 2023)
Many studies highlight human and physical capital’s role in the emergency response and post-disaster recovery phases. Even though social capital also plays a major role in emergency response and disaster recovery. Social capital can reduce disaster risk at the community level, especially for those who live in disaster areas. For this reason, the role of social capital in the emergency response and recovery phase is important, and its utilization must be developed. This study is expected to provide an overview of the role and influence of social capital in emergency response and post-disaster recovery in two different settings, both geographically and in the type of disaster that occurred. The research was conducted using a qualitative approach with a systematic literature review method, data collection was carried out by collecting literature, studies, articles, journals, reports, and previous research related to the role of social capital in post-disaster recovery process. The cases in this study are the eruption in Eyjafjallajökull in Iceland and the earthquake in Gili Trawangan, Indonesia. This review focuses on three forms of social capital, bonding, bridging, and linking, available in disaster-affected communities and how these forms of social capital affect the recovery process of communities affected by disasters. The results show that in both areas, bonding social capital plays the strongest role, but there are differences in the impact of disasters on the condition of social capital in both area.